Rekonfigurasi Jaringan Distribusi Akibat Kontingensi Menggunakan Metode Binary Integer Programming (Studi Kasus : Sistem Distribusi 20 kV Surabaya) - Aji Akbar Firdauas (Jurnal Teknologi Terpadu, 2018)
On the distribution network, there are some problems. The problem is losses, contingency. Contingencies and losses can be solved with network reconfiguration. In this research, the reconfiguration of the distribution network is done by Binary Integer Programming (BIP) method. This network reconfiguration is done on Surabaya's 20 kV distribution system. From the simulation results, reconfiguration can solve the problems caused by contingency appropriately and optimally. With the implementation of this system, losses and financial losses can be minimized and system reliability can be improved.